134k views
0 votes
F(x)=e^2x-4
Determine inverse of given function

User Henry B
by
5.9k points

1 Answer

4 votes

Answer:


f^(-1)(x)=(1)/(2)ln(x)+2

Explanation:

Start by changing the f(x) into a y. Then switch the x and the y. Then solve for the new y. Like this:


y=e^(2x-4) becomes


x=e^(2y-4)

To solve for the new y, we need to get it out of its current exponential position which requires us to take the natural log of both sides. Since a natural log has a base of e, natural logs and e's "undo" each other, just like taking the square root of a squared number.


ln(x)=ln(e)^(2y-4)

When the ln and the e cancel out we are left with

ln(x) = 2y - 4. Add 4 to both sides to get

ln(x) + 4 = 2y. Divide both sides by 2 to get


(1)/(2)ln(x) + 4 = y.

Since that is the inverse of y, we can change the y into inverse function notation:


f^(-1)(x)=(1)/(2)ln(x)+4

User Jake Reece
by
6.0k points